METHOD TO ESTIMATE THE SYSTEM PROBABILITY OF FAILURE FOR SLOPE STABILITY ANALYSIS (GEOMATE Journal, 2018)
Uncertainty in soil slope is one of the problems in slope stability analysis because natural soilslope is heterogeneous that is difficult to predict time and location of the failure. This problem leads that onlyconventional approaches do not take into account many risks related to slope safety. The optimization of thisproblem is carried out using probabilistic slope stability analysis. This paper described a method to calculatethe probability of failure of slope stability analysis. The system probability of failure is defined as thecomplement of the sum of the probability of failure corresponding to sliding failure. Furthermore, this papershows time-steps in the developments of factors of safety in soil slope and perform natural slope stabilityanalyses by probabilistic approach on a hill range. Sensitivity result indicated that the effective angle ofinternal friction (φ) and the angle of soil slope (β) are most significant parameters and choose to be randomvariable parameters. Probabilistic for soil slope failure is calculated using conventional design equations,mean and coefficient of variation values for the random variable parameters as input. GeoStudio’s program(SEEP/W and SLOPE/W application) have been employed to describe the process of rainfall infiltrationunder positive and negative pore-water pressures and slope stability analyses, respectively. Bishop’ssimplified method was used in conjunction with Monte Carlo Simulation to determine in term of theprobability of failure (Pf). This approach is to prove the best confidence result in slope stability analysis.